Self-regulation in the classroom : helping students learn how to learn - Cash, Richard M. (Free Spirit Publishing, 2016)
To succeed in school, students need more than subject area knowledge--they must learn how to learn. Self-regulation, an executive functioning skill, describes the ways that students focus attention on achieving success. Self-regulated learners find personal value in learning, develop effective study habits, welcome challenges, seek help, and use failure as a learning tool. This user-friendly guide makes the process of developing self-regulation as easy as ABC: Affect (how you feel), Behavior (what you do), and Cognition (how you think). Teaching students to balance these three elements builds motivation, resilience, and college and career readiness. Digital content includes customizable forms from the book.- Resumé vydavatel